2019
DOI: 10.1155/2019/2590563
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Healthcare-Associated Infections on Length of Stay: A Study in 68 Hospitals in China

Abstract: Healthcare-associated infections (HAIs) not only bring additional medical cost to the patients but also prolong the length of stay (LOS). 2119 HAI case-patients and 2119 matched control-patients were identified in 68 hospitals in 14 primary sampling provinces of 7 major regions of China. The HAI caused an increase in stay of 10.4 days. The LOS due to HAI increased from 9.7 to 10.9 days in different levels of hospitals. There was no statistically significant difference in the increased LOS between different hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 30 publications
6
46
1
1
Order By: Relevance
“…Healthcare-associated infections (HAIs) are known worldwide as a public health problem, which have led to a significant increase in mortality, morbidity, and cost of patient care due to longer stays [1]. Their frequency and severity are particularly high in the intensive care settings because of the pathologies presented by the patients, the associated comorbidities, and the density of the invasive techniques used [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare-associated infections (HAIs) are known worldwide as a public health problem, which have led to a significant increase in mortality, morbidity, and cost of patient care due to longer stays [1]. Their frequency and severity are particularly high in the intensive care settings because of the pathologies presented by the patients, the associated comorbidities, and the density of the invasive techniques used [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In Jia et al’s recent study, which was undertaken across 68 hospitals, the results suggested that LOS may be influenced by an organism’s sensitivity to antibiotics. For non-drug-resistant organism infections, the LOS was 12.2 days, whereas it was 14 days for multi-drug-resistant organism infections in hospital-acquired bloodstream infections [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MDRO infection will prolong the hospital stays of patients [28]. A study on the impact of hospital infections on the LOS in 68 hospitals in China found that MDRO infection increased the average LOS by one day, and the maximum number of days for CR-PA infection increased by 26 days [29]. Langeveld [30] also found that the MDRO group had an average of 25 more hospital stays than the non-resistant group.…”
Section: Discussionmentioning
confidence: 99%